Karakteristik pengelolaan model pendidikan berbasis pesantren - Jumardhi,; Ansar, Ahlun; Oktafia, Nurul Afni; Malik, Nurhaliza; Arismunandar, (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
Pesantren as a traditional Islamic educational institution has a strategic role in shaping the character and morals of the nation's generation amid the dynamics of educational modernization. This research aims to describe the education unit model as well as pesantren education management practices in Indonesia with a case study of Darul Aqram Muhammadiyah Gombara Islamic Boarding School in Makassar. The research used a qualitative approach with descriptive methods, through data collection techniques in the form of observation, in-depth interviews, and documentation to obtain a comprehensive picture of the pesantren management system. The results showed that Darul Aqram Muhammadiyah Gombara Islamic Boarding School Makassar is a modern Islamic boarding school that integrates four curricula, including the national curriculum and Muhammadiyah's unique curriculum. This pesantren has excellent programs, such as Tahfidzul Qur'an, mastery of Arabic and English, leadership development, and literacy movement to increase students' interest in reading. The santri development process takes place for almost 24 hours with an emphasis on strengthening religious values, classical book studies, and discipline. However, the pesantren faces challenges in the form of differences in santri backgrounds that have the potential to cause misunderstandings in social interactions. Overall, the management of this pesantren shows adaptive efforts in combining traditional values and the demands of modern education. Abstrak Pesantren sebagai lembaga pendidikan Islam tradisional memiliki peran strategis dalam pembentukan karakter dan moral generasi bangsa di tengah dinamika modernisasi pendidikan. Penelitian ini bertujuan untuk mendeskripsikan model satuan pendidikan serta praktik manajemen pendidikan pesantren di Indonesia dengan studi kasus Pondok Pesantren Darul Aqram Muhammadiyah Gombara Makassar. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif, melalui teknik pengumpulan data berupa observasi, wawancara mendalam, dan dokumentasi untuk memperoleh gambaran yang komprehensif mengenai sistem pengelolaan pesantren. Hasil penelitian menunjukkan bahwa Pondok Pesantren Darul Aqram Muhammadiyah Gombara Makassar merupakan pesantren modern yang mengintegrasikan empat kurikulum, termasuk kurikulum nasional dan kurikulum khas Muhammadiyah. Pesantren ini memiliki program unggulan, seperti Tahfidzul Qur’an, penguasaan Bahasa Arab dan Inggris, pengembangan kepemimpinan, serta gerakan literasi untuk meningkatkan minat baca santri. Proses pembinaan santri berlangsung hampir selama 24 jam dengan penekanan pada penguatan nilai-nilai keagamaan, kajian kitab klasik, dan kedisiplinan. Namun demikian, pesantren menghadapi tantangan berupa perbedaan latar belakang santri yang berpotensi menimbulkan kesalahpahaman dalam interaksi sosial. Secara keseluruhan, manajemen pesantren ini menunjukkan upaya adaptif dalam memadukan nilai tradisional dan tuntutan pendidikan modern.